2008
DOI: 10.19182/remvt.9991
|View full text |Cite
|
Sign up to set email alerts
|

Influence du type de complément énergétique (rebuts de dattes <em>vs</em> orge) sur les performances d’engraissement et caractéristiques des carcasses d’agneaux Berbères à l’engraissement

Abstract: La valorisation des ressources locales dans les aliments d’animaux en croissance, lorsque celles-ci sont disponibles en quantités appréciables, peut être une opportunité pour réduire les coûts de production et sécuriser le système d’engraissement. Le maintien des performances zootechniques reste toutefois un préalable. Une expérience a porté sur quatre lots de dix agneaux recevant des rations isoprotéiques dans lesquelles des rebuts de dattes ont été incorporés en proportions variables en substitution à l’orge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Linear and weight measurements enabled calculating the compactness indexes which confirmed the subjective conformation observed. Furthermore these results showed that Beni-Guil carcasses exhibited good compactness indexes (LCI and CCI2) compared to those reported by Mebirouk-Boudechiche et al (2008) for the Berber Algerian breed. Nevertheless, LCI, CCI1 and CCI2 values for Beni-Guil sheep were lower than those reported by Alexandre et al (2008) for the Martinik French breed.…”
Section: Subjective Carcass Characteristicssupporting
confidence: 51%
“…Linear and weight measurements enabled calculating the compactness indexes which confirmed the subjective conformation observed. Furthermore these results showed that Beni-Guil carcasses exhibited good compactness indexes (LCI and CCI2) compared to those reported by Mebirouk-Boudechiche et al (2008) for the Berber Algerian breed. Nevertheless, LCI, CCI1 and CCI2 values for Beni-Guil sheep were lower than those reported by Alexandre et al (2008) for the Martinik French breed.…”
Section: Subjective Carcass Characteristicssupporting
confidence: 51%
“…Waste dates are conventionally used as supplementary feed for livestock in southern Algeria (Boudechiche et al, 2008). Waste dates are a rich in carbohydrates, dietary fiber and minerals, with lower contents in lipids and protein (Sidhu, 2006).…”
Section: Introductionmentioning
confidence: 99%